Elevated aerosols and role of circulation parameters in aerosol vertical distribution. (January 2016) - Prijith, S.S.; Aloysius, Marina; Mohan, Mannil; Rao, P.V.N.
Abstract: The study examines aerosol loading in different vertical layers of the atmosphere and explores the role of atmospheric circulation parameters in vertical distribution of aerosols and in its seasonal variability. Aerosol vertical distribution over the globe is examined, using long term satellite observations, by considering aerosol loading in different layers of atmosphere upto ∼6 km altitudes from surface and fractional contribution of each of these layers to total columnar aerosol loading. Aerosols are observed residing close to the surface in most of the oceanic environments, except over certain regions which are in the close proximity of continents where upper level winds are conducive for long range aerosol transport. In contrast, considerable vertical spread in aerosol distribution with strong seasonal variability, minimum occurring in winter months and maximum in summer, is observed over the continental regions. Vertical spread in aerosol distribution is observed highest over north eastern and north western parts of Africa during northern hemispheric summer, when the convection activity peaks over these regions due to large solar insolation and associated surface heating. Seasonal variation of aerosol vertical spread over both of these regions is observed in phase with variation in atmospheric convergence and vorticity. During summer months, when the aerosol vertical spread is highest, strong surface level convergence and associated cyclonic vorticity is observed along with an upper level (700–600 hPa) divergence. The surface level convergence and upper level divergence together induce an upward flow of air which carries aerosols from ground to higher altitudes. This mechanism of aerosol vertical transport is further corroborated through the correlation and regression relations of surface convergence/vorticity with aerosol loading above different elevations and hence the study reveals role of circulation parameters in aerosol vertical distribution. Highlights: Global aerosol loading in different vertical layers of the atmosphere is examined. Investigates role of circulation parameters in aerosol vertical distribution. Aerosol vertical spread is in phase with surface wind convergence and vorticity. Vertical span of aerosol spread is maximum in summer and minimum in winter.